O lugar do crime no jornal: uma análise da cobertura policial do Jornal da Paraíba - Silva, Valéria Sinésio da (2016)
Death has frequently been a piece of news present in newspapers. In fact, some might say that journalism would not survive the lack of police occurrences which are becoming ever more frequent due to the increase of urban violence indexes that seem not to select race, gender or social status. Nevertheless, what is observed is that there are distinct spaces for these pieces of news in the papers. On no account will some deaths ever hog the headlines, whereas others will have special media coverage, with reporters covering the police investigation steps as well as demanding celerity in the Justice processes. In this perspective, we have yet observed that the treatment given to the coverage of these cases rules police journalism, which may contribute to the banalization of violence and an omitted media in its role to claim on efficient public polices from the administrators. News publication as an extension of police reports frequently leaves the victim’s name uninformed, thus turning them invisible to the readers. Given this context, it gives the impression that the vast majority of deaths bother neither the press nor society, consequently. On the other hand, when violence reaches the noblest layers and notorious prominent people, crime has far-reaching repercussion. In order to reach this understanding, we have referred to methods of Speech Analysis (SA) and Content Analysis (CA) which have allowed us to decode the meaning of words as well as the recurrence of terms and elements that claim to this distinction between what we call the illustrious and invisible dead in the Jornal da Paraíba. Our study aims at understanding what the criteria is in this journalistic process, in which these victims of violent crimes tend to either be immortalized or minimized, according to the type of coverage given and the form that this piece of news is treated in the paper. In the extract analysed, it was possible to observe that crime coverage apart from being superficial, it most often disrespects the victims of violent crimes using biased expressions in place of their names, thus, somehow being attempts, though unconscious, to justify their deaths. At last, we understand that this crime coverage lacks, as well as the Police themselves, investments and better staff training